Analysis of novel ultrasonic tips for the instrumentation and removal of filling material in flattened/oval-shaped root canals: a micro-computed tomographic study - Peña, Melissa Esther Rivera (2018)
Aim: To analyse the influence of novel ultrasonic tips on the instrumentation and removal of filling material in flattened/oval-shaped canals. Methodology: Forty-five mandibular incisors were selected and randomly divided into three experimental groups according to different protocols. For the instrumentation procedures, the following protocols were used: Group PFCP: ProDesign Logic 25/.05 + Flatsonic + Clearsonic + Prodesign Logic 40/.01, Group FCP: Flatsonic + Clearsonic + ProDesign Logic 40/.01 and Group PP: Prodesign Logic 25/.05 + Prodesign Logic 40/.05. After the instrumentation procedures, the samples were randomly divided into three experimental groups for the removal of filling material: Group R: Reciproc R25/.08, Group RC: Reciproc R25/.08 + Clearsonic tip and Group CR: Clearsonic tip + Reciproc R25/.08. The teeth were scanned pre and post-operatively by the means of a micro-computed tomography system. The percentage values for increase in volume, non-instrumented surface area, dentine removal, degree of canal transportation, centering ratio and percentage of residual filling material between the experimental groups were examined. Data were analysed using non-parametric Kruskal-Wallis and Dunn\'s tests. The significance level was of P<0.05. Results: The instrumentation technique applied in group PFCP provided the greatest volume increase in the total portion of the root canal, showing the lowest percentage of noninstrumented surface area. Regarding the degree of transportation in the buccolingual direction, statistically significant differences between groups PFCP and PP were observed in the coronal third of the canal. In the mesio-distal direction, no statistically significant differences in the coronal, middle and apical thirds were observed. As for the centering ratio, statistically significant differences were found in the bucco-lingual direction. In the mesio-distal direction, no statistically significant differences in the coronal, middle and apical thirds were observed between the instrumentation protocols used in this study. Statistically significant differences between the experimental groups were found in the total portion of the root canal, where group R provided the highest percentage of residual root canal filling material when compared to groups RC and CR. In group C, the lowest percentage of residual root canal filling material was observed. Concerning the percentage of residual root canal filling material in the apical third of the root canal, statistically significant differences were found between the different protocols used in this study. The technique used in group CR, provided the lowest percentage of residual root canal filling material. Conclusions: The protocol used in the PFCP group provided a significant increase in volume and reduced the percentage of non-instrumented walls during the shaping of oval-shaped canals. The use of the ClearSonic tip as the first instrument followed by the Reciproc 25/.08 file for the removal of filling material, resulted in the lowest percentage of residual filling material in the total portion and in the apical third of the root canal.